PERKEMBANGAN DEPOSITO BERJANGKA SEBAGAI SALAH SATU SUMBER DANA PIHAK KETIGA : Pada Bank Rakyat Indonesia Cabang Gatot Subroto - Nikma Apriliani (2021)
Bank Rakyat Indonesia Gatot Subroto Branch is one of the financial institutions in Indonesia that can serve the needs and launch mechanisms in the economic sector, one of which is by collecting or obtaining deposit funds from the public (third party funding sources) in the form of demand deposits, savings and time deposits. This aims to increase the bank's sources of funds, so that operational activities can run smoothly. Time deposits are one of the banking products that are enjoyed by many customers and are a source of funds that are one of the mainstays for banks. In another sense, time deposits are third party deposits to banks whose withdrawals can be made within a certain period of time according to an agreement between a third party and a bank or based on a deposit agreement. In this opportunity, the author conducted research at Bank Rakyat Indonesia Branch Gatot Subroto. The author's purpose in writing this thesis is to find out the development of the amount of funds collected by the Gatot Subroto Branch of Bank Rakyat Indonesia and to determine the amount of time deposits collected by the Gatot Subroto branch of Bank Rakyat Indonesia. Thus the results of the final project show that the sources of third party funds in the form of savings deposits, current accounts and time deposits collected by Bank Rakyat Indonesia Gatot Subroto Branch have increased every year (2018 to 2020). The amount of funds that can be raised by Bank Rakyat Indonesia Gatot Subroto Branch in 2018 to 2020 is 81.93% in 2018 to Rp.8,455,000,000,- in 2019 it is 74.19% to Rp.8,575,000,000,- while in 2020, which is 74.42% to Rp. 13,925,000,000,-. At Bank Rakyat Indonesia Branch Gatot Subroto Time deposits are a source of third party funds that have the largest amount of funds compared to savings and current accounts.